2014
DOI: 10.1007/s00213-014-3708-x
|View full text |Cite
|
Sign up to set email alerts
|

A single exposure to cocaine during development elicits regionally-selective changes in basal basic Fibroblast Growth Factor (FGF-2) gene expression and alters the trophic response to a second injection

Abstract: These findings show that a single cocaine injection is sufficient to produce enduring changes in the adolescent brain and indicate that early cocaine priming alters the mechanisms regulating the trophic response in a brain region-specific fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Our previous study found that adolescent cocaine exposure results in a prolonged modification on synapses in adult medial prefrontal cortex (mPFC) (6). A single cocaine injection could produce changes in the mPFC of adolescent rather than adult animals (7,8), indicating that adolescent mPFC is more sensitive to cocaine experience than that of adults (9,10). Subregions of mPFC, mainly including cingulate cortex, prelimbic cortex (PrL), and infralimbic cortex, demonstrate distinct connectivity and regulate different behavioral outcomes (11).…”
mentioning
confidence: 99%
“…Our previous study found that adolescent cocaine exposure results in a prolonged modification on synapses in adult medial prefrontal cortex (mPFC) (6). A single cocaine injection could produce changes in the mPFC of adolescent rather than adult animals (7,8), indicating that adolescent mPFC is more sensitive to cocaine experience than that of adults (9,10). Subregions of mPFC, mainly including cingulate cortex, prelimbic cortex (PrL), and infralimbic cortex, demonstrate distinct connectivity and regulate different behavioral outcomes (11).…”
mentioning
confidence: 99%
“…These findings add complexity as well as specificity to our previous data and reinforce the notion that a single cocaine exposure during adolescence is sufficient to trigger functional and structural changes in the rat brain. We have previously shown that a single injection of cocaine during adolescence influences the response to a second challenge of the psychostimulant, altering trophic response (Giannotti et al, 2015) as well as actin dynamics (Caffino et al, 2017b) thus suggesting that early cocaine priming might affect plasticity in the developing brain. Further studies will evaluate whether a single exposure to cocaine during adolescence influences addiction liability at adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Since adolescence is considered a window of vulnerability to drugs of abuse, we have recently investigated whether a single exposure to cocaine during this exquisitely sensitive maturational period would be sufficient to alter brain plasticity. We have found that a single cocaine exposure alters expression of neurotrophic factors such as FGF-2 (Giannotti et al, 2015) and disrupts actin dynamics (Caffino et al, 2017b). Based on these lines of evidence, we hypothesized that a single injection of cocaine during adolescence would be sufficient to trigger enduring morphological changes in the developing brain, altering the glutamate synapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some genes involved in compensatory adaptive changes might display gene priming, reflecting graded levels of epigenetic regulation, and transcription-based changes in protein abundance might modify the redox-regulated pathways indicated in Figure 2 . Recent advancements (Anker and Carroll, 2011 ; Robison and Nestler, 2011 ; Schwarz et al, 2011 ; Feng and Nestler, 2013 ; Giannotti et al, 2014 ; Li et al, 2014 ) clearly indicate the potential value of investigating the various mechanisms that modulate the reversible transitions between chromatin states under the influence of drug exposure, including gene priming and desensitization.…”
Section: Gene Primingmentioning
confidence: 99%